Pemetaan Tata Guna Lahan dengan Metode Supervised Classification - Qur'ani, Mutiara Nurul; Romdania, Yuda; Zakaria, Ahmad; Herison, Ahmad (Universitas Lampung, 2023)
Land use is used to determine the effect of community activities on the land use of an area. Currently, the search for land use information can be reviewed periodically with remote sensing technology. The aim of the research is to map land use and provide information to the public regarding the condition of land use in the Way Pubian Sub-watershed area. The method used in processing land mapping data is supervised classification based on the training samples that have been collected. The supervised classification method is available in ArcGIS software. The method of analysis refers to descriptive analysis, by describing the land use maps obtained. The results of the map show that land use in the Way Pubian Sub-watershed consists of ponds of 1.57 Ha with a percentage of land of 0.01%, forest land of 6719.14 Ha of a percentage of 57.83%, open land area of 122.58 Ha of percentage 1.06%, settlements 823.2 Ha a percentage of 7.08%, Plantations 2783.11 Ha a percentage of 23.95% and paddy fields 1169.34 Ha with a land percentage of 10.06%. Compared to Landsat imagery, map making is more effective if using high-resolution imagery, then Google Earth imagery is used as data processing material. The conclusion obtained by processing data with ArcGIS software helps in mapping land use, obtaining the area and percentage of land use. The percentage results show that the largest land use is forest land and the smallest land area is pond land.Keywords: map, land use, watershed, GIS, imagery